Generalized Fractional Integral Inequalities for $(h,m,s)$-Convex Modified Functions of Second Type - Juan Napoles Valdes; Bahtiyar Bayraktar (Sahand Communications in Mathematical Analysis)
New variants of the Hermite - Hadamard inequality within the framework of generalized fractional integrals for $(h,m,s)$-convex modified second type functions have been obtained in this article. To achieve these results, we used the Holder inequality and another form of it - power means. Some of the known results described in the literature can be considered as particular cases of the results obtained in our study.